The effect of Edaravone on clinical symptoms and oxidative stress factors in patients with acute ischemic stroke: A clinical trial - Mojtaba Khazaei; Fatemeh Saadati Pour; Masoud Ghiasian; Salman Khazaei; Shahir Mazaheri; Akram Ranjbar; Sajjad Daneshyar; Mozhgan Nazifi (مجله علوم پزشکی فیض (پیوسته))
Background and Aim: Edaravone is known for its efficacy in inhibiting free radical formation, activating microglia, and promoting neurogenesis and neuroprotection following acute ischemic stroke. This clinical trial aimed to investigate the effects of Edaravone on clinical symptoms and oxidative stress factors in patients with acute ischemic stroke. Methods: In this clinical trial, fifty-two patients diagnosed with acute ischemic stroke were randomly assigned to receive either Edaravone (120 mg daily up to 3 doses intravenously) or a placebo in addition to standard treatment. Stroke severity was assessed using the NIH Stroke Scale (NIHSS) and Modified Rankin Scale (MRS) at hospitalization and three months post-stroke. Antioxidant capacity, protein oxidation, and lipid peroxidation levels were measured during hospitalization and three days later. Results: Twenty-six patients were included in each group and were matched in terms of risk factors, neurological symptom severity, antioxidant capacity, protein oxidation, and lipid peroxidation at hospitalization. At the three-month follow-up, both groups showed a decrease in neurological symptom severity, with a slightly higher reduction observed in the Edaravone group, though not statistically significant (P=0.256). A similar proportion of patients achieved an MRS score of ≤2 within three months post-stroke in both groups (23.1% in the placebo group vs. 30.8% in the Edaravone group, P=0.755). All eight deaths within the first three months occurred in the placebo group. The most common side effect was intracerebral hemorrhage (13.5%), predominantly in the placebo group. Despite higher mean antioxidant capacities in the intervention group, no significant difference was observed post-intervention. Conclusion: The study suggests that adding Edaravone to standard treatment for acute ischemic stroke may lead to improved patient outcomes. However, further research with larger sample sizes is needed to establish the efficacy of this medication.